Common Indications and The Diagnostic Yield of Esophagogastroduodenoscopy in Children with Gastrointestinal Distress - Aydin, Malik; Niggeschmidt, Judith; Ballauff, Antje; Wirth, Stefan; Hensel, Kai O. (Klinische Pädiatrie, 2019)
Background The number of inconspicuous results of esophagogastroduodenoscopies (EGDs) in childhood appears to be disturbingly high. The aim of this study was to analyze the diagnostic yield of EGD and to determine its relevance of specific clinical indications.Methods We performed a retrospective analysis of 380 consecutive pediatric patients who underwent diagnostic EGD in two German level I pediatric gastroenterology departments in 2015 and 2016.Results 44% of the 380 patients were male and 17% were younger than 5 years old. 55% of all EGDs (n=210) did not yield a pathological result. 27% (n=104) of all EGDs were performed due to nonspecific symptoms (epigastralgia, nausea). Strikingly, in this group, 88% (n=91) showed normal results and in only 12% a diagnosis was made: reflux esophagitis (n=5), Helicobacter pylori (HP) gastritis (n=6) or hemorrhagic gastritis (n=1). Fewer inconspicuous EGDs were performed in patients with dysphagia (68%) or heartburn and reflux (61%). 59 patients were examined due to serologically elevated celiac antibodies. Here, the diagnosis could be confirmed histopathologically in 78% (n=46). Of the 37 patients with abdominal pain and a previously positive non-invasive HP test, EGD served to establish the diagnosis of HP gastritis in 84%.Conclusions The diagnostic yield for EGDs is increased in patients with more specific symptoms (i. e. dysphagia, heartburn, HP, celiac disease). Consequently, as an invasive procedure, EGD warrants a strict indication.
Keywords: esophagogastroduodenoscopy; indication; Helicobacter pylori; dysphagia; reflux; abdominal pain